Coordination Cartesian Model In Disaster Management (Study at BPBD North Luwu Regency) - Yamin, Muhammad Nur; Tarri, Afra Marlin; Ismail, Ismail; Aina, Asri Nur (Jurnal Aktor, 2023)
This research aims to determine Cartesian Model Coordination in Disaster Management (Study at BPBD North Luwu Regency). This type of research is qualitative with data collection techniques carried out by means of observation, interviews, documentation. The data analysis technique used consists of data reduction, data presentation and drawing conclusions.The research results show that many factors influence the level of success of coordination in supporting the effectiveness of BPBD for disaster management in North Luwu Regency. The cooperative relationship between relevant agencies in handling regional disasters is felt to be still less than optimal and effective because rehabilitation, environmental improvement in disaster areas and health rehabilitation are in the not optimal category because rehabilitation activities carried out in the community have not been completed thoroughly due to the lack of available disaster budget, BPBD is less firm and it is clear that the relevant agencies refer more to their previous regulations, and in supervision there is almost no coordination, especially in the form of supervision, informing each other in the form of reports resulting in ineffective work plans that have been made because they are still thinking about personal or group interests that are sectoral ego.